A systematic review and meta‐analysis of COVID‐19 in kidney transplant recipients: Lessons to be learned. Issue 12 (19th July 2021) - Kremer, Daan; Pieters, Tobias T.; Verhaar, Marianne C.; Berger, Stefan P.; Bakker, Stephan J. L.; van Zuilen, Arjan D.; Joles, Jaap A.; Vernooij, Robin W. M.; van Balkom, Bas W. M.
Abstract : Kidney transplant recipients (KTR) may be at increased risk of adverse COVID‐19 outcomes, due to prevalent comorbidities and immunosuppressed status. Given the global differences in COVID‐19 policies and treatments, a robust assessment of all evidence is necessary to evaluate the clinical course of COVID‐19 in KTR. Studies on mortality and acute kidney injury (AKI) in KTR in the World Health Organization COVID‐19 database were systematically reviewed. We selected studies published between March 2020 and January 18th 2021, including at least five KTR with COVID‐19. Random‐effects meta‐analyses were performed to calculate overall proportions, including 95% confidence intervals (95% CI). Subgroup analyses were performed on time of submission, geographical region, sex, age, time after transplantation, comorbidities, and treatments. We included 74 studies with 5559 KTR with COVID‐19 (64.0% males, mean age 58.2 years, mean 73 months after transplantation) in total. The risk of mortality, 23% (95% CI: 21%–27%), and AKI, 50% (95% CI: 44%–56%), is high among KTR with COVID‐19, regardless of sex, age and comorbidities, underlining the call to accelerate vaccination programs for KTR. Given the suboptimal reporting across the identified studies, we urge researchers to consistently report anthropometrics, kidney function at baseline and discharge, (changes in) immunosuppressive therapy, AKI, and renal outcome among KTR. Abstract : This systematic review and meta‐analysis on COVID‐19 in kidney transplant recipients reveals high global mortality rates and provides recommendations for reporting of studies in future pandemics.